Sulfur Use Efficiency Is a Significant Determinant of Drought Stress Tolerance in Relation to Photosynthetic Activity in Brassica napus Cultivars - Lee, Bok-Rye; Zaman, Rashed; Avice, Jean-Christophe; Ourry, Alain; Kim, Tae-Hwan (Frontiers in Plant Science, 2016)
To investigate the varietal difference in sulfur use efficiency (SUE) and drought stress tolerance, Brassica napus ‘Mosa’ and ‘Saturnin’ were exposed to polyethylene glycol (PEG)-induced drought stress for 72 h. Direct quantification of S uptake, de novo synthesis of amino acids and proteins was performed by tracing 34S. The responses of photosynthetic activity in relation to SUE were also examined. The total amount of newly absorbed S decreased with drought stress in both cultivars but the decrease rate was significantly higher in Mosa (-64%) than in Saturnin (-41%). Drought stress also decreased the amount of S assimilated into amino acids (34S-amino acids) and proteins (34S-proteins). The total amount of S incorporated into amino acids and proteins was generally higher in Saturnin (663.7 μg S per plant) than in Mosa (337.3 μg S per plant). The estimation of SUE based on S uptake (SUpE) and S assimilation (SUaE) showed that SUE was much higher in Saturnin than in Mosa. The inhibition of photosynthetic activity including Rubisco protein degradation caused by drought stress was much lower in the cultivar with higher SUE (Saturnin). The present study clearly indicates that the genotype with higher SUE is more tolerant to PEG-induced drought stress.